Bartering for a better future? Community currencies and sustainable consumption - Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2004)
Sustainable consumption is gaining currency as a new policy objective, requiring consumers to enact preferences for sustainability through the marketplace. But there is a limit to the changes in consumption behaviour which individuals can make within social institutions, and current policies do not question the materialism inherent in current development policies. New social institutions, or structures of provision, are needed to enable the lifestyle changes required for sustainability. This paper critically assesses the potential of one such alternative system of provision: namely money and exchange. 'Community currencies' is the generic term for a wealth of alternative types of money which are springing up in communities throughout the world to address social, economic and environmental needs. This paper presents new research findings and reviews experience of three distinct types of community currency with goals of sustainable consumption, each with a different purpose and design, and assess their potential as new institutions for environmental governance. The currencies examined are: Local Exchange Trading Schemes (LETS) which aims to rebuild local economies through cashless exchange; Time Banks promote volunteering, civic engagement and mutual self-help by rewarding unpaid work in the community; the previously unresearched NU-card, a mainstream 'green loyalty point' currency piloted in the Netherlands which incentivises sustainable consumption. This paper discusses the scope and potential of each of these models, the values they represent and the barriers they face, and will suggest possible ways forward for creating new social infrastructure for sustainable consumption.
Keywords: 330; community currencies; governance; institutions; LETS; sustainability; time banks; Tauschwirtschaft; Alternative Ökonomie; Nachhaltige Entwicklung